Differences in types of artificial cranial deformation are related to differences in frequencies of cranial and oral health markers in pre-Columbian skulls from Peru - Okumura,Mercedes (2014)
Artificial cranial deformation is a cultural practice that modifies the shape of the skull during the early infancy. It is not related to rites of passage, but to different social status in a group. Therefore, the deformed cranium is an expression of individual affirmation and affiliation to a given social group. Osteological material from Pasamayo (AD 1200-1450), a cemetery in central coast of Peru, was analyzed to test whether individuals presenting different types of cranial deformation (interpreted as a sign of different social status) present differences in health status. Three types of cranial deformation were observed and five osteological markers (cribra orbitalia, cranial trauma, antemortem tooth loss, dental caries, and periodontal cavities) related to health status were analyzed in 78 crania. No significant differences were found in terms of these osteological markers among females in relation to the different types of cranial deformation. However, males presenting occipital deformation had significantly less caries and periodontal cavities than the others. Moreover, males presenting fronto-lambdoid deformation had more antemortem tooth loss than the other males. Therefore, although different types of cranial deformation can be potentially associated to distinct social status, differences in health status could only be observed in the male sample.